Strategi Pengembangan Usaha dalam mengenalkan UMKM “Renyah Kepiting Borneo” melalui Pembuatan Video Profil Usaha dan Inovasi Produk dalam meningkatkan Daya Saing UMKM di Sentra Industri Kecil, Teritip Balikpapan - Berlianti, Nadya; Darrens, Andreans Figo; Sa’idah, Elly; Sari, Intan Sapitri Permata; Jaya, M. Rifki Refian; Prihanisetyo, Adi (STIE Pelita Nusantara, 2024)
Field Work Practice (PKL) or also known as Innovation Development (PI) is a service activity of STIE Madani students to the community, especially to Micro, Small and Medium Enterprises (MSMEs). On this occasion, group 11 PI students of STIE Madani Balikpapan provided assistance in one of the villages in Balikpapan City, namely Teritip Village. The target of MSMEs targeted in the Innovation Development Program (PI) this time is the